2021
DOI: 10.1002/advs.202004987
|View full text |Cite
|
Sign up to set email alerts
|

Physiology‐Based Stretchable Electronics Design Method for Accurate Surface Electromyography Evaluation

Abstract: Stretchable electronics-based surface electromyography (sEMG) evaluation devices are expected to play a big role in clinical diagnosis. However, the stability and quality of the signals collected by existing stretchable electronics are too poor, especially when muscle movement is involved, making them inappropriate for high standard clinical diagnosis. Here, a physiology-based design method for stretchable electronics and a novel airbag-type stretchable electrode array (ASEA) device for assessment of the compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
(66 reference statements)
0
5
0
Order By: Relevance
“…This configuration ensures a stable probe-muscle contact interface, and is able to follow the movement of muscle during muscle contraction, so that the ASEA can collect high-quality sEMG signals [ 27 , 28 ]. The fabrication process and details of the ASEA device are presented in our previous paper, and the results have demonstrated that the accuracy and stability of ASEA device are far superior to existing PFM electrode probes [ 22 ]. The design comparison between ASEA-based sEMG acquisition method and existing technologies can be found in Note S1, Figure S1 and Table S1 (Supplementary Materials) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This configuration ensures a stable probe-muscle contact interface, and is able to follow the movement of muscle during muscle contraction, so that the ASEA can collect high-quality sEMG signals [ 27 , 28 ]. The fabrication process and details of the ASEA device are presented in our previous paper, and the results have demonstrated that the accuracy and stability of ASEA device are far superior to existing PFM electrode probes [ 22 ]. The design comparison between ASEA-based sEMG acquisition method and existing technologies can be found in Note S1, Figure S1 and Table S1 (Supplementary Materials) .…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we developed a multifunctional evaluation technology (MET) based on an airbag-type stretchable probe (ASEA) [ 22 ] to diagnose the malfunctions of regional PFM. The ASEA is able to be inflated, so that it can fit vaginal cavities of different sizes and shapes.…”
Section: Introductionmentioning
confidence: 99%
“…Conformal printing on curved surfaces involves techniques like electrohydrodynamic (EHD) jet printing [31][32][33], aerosol jet printing [34][35][36], inkjet printing [37][38][39][40], laser direct writing [41][42][43][44][45], and adaptive 3D printing [46]. For example, EHD jet printing on irregular or rough three-dimensional surfaces faces challenges due to the real-time variation of electric field strength, leading to unstable jets and difficult-to-achieve high-precision and stable printing on complex surfaces [47][48][49]. Aerosol jet printing is limited by material viscosity and poor wire edge roughness, resulting in poor electrical performance consistency [50].…”
Section: Introductionmentioning
confidence: 99%
“…Flexible and stretchable electronic devices with excellent mechanical properties adaptable to the skin have tremendous advantages in healthcare applications, especially in the field of neuroprosthetics [1][2][3][4] . Surface electromyography (sEMG) sensors that record muscle signals on the skin are used as a clinical indicator to help with rehabilitation and treat diseases in a noninvasive manner 5,6 .…”
Section: Introductionmentioning
confidence: 99%